EKSISTENSI PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM - Sadali Sadali (Atta'dib Jurnal Pendidikan Agama Islam, 2020)
Islamic education institutions in pesantren are the most important foundations and pillars for building Islamic civilization in Indonesia. Islamic boarding schools are known as the strongholds of the Islamic ummah and the center of the spread of Islam as well as the advancement of Muslims. As a religious, educational and social institution, Islamic boarding schools must be preserved and developed in order to produce quality Muslim intellectuals with good morals. It is the pesantren that determines the Islamic society and plays the most important role for the spread of Islam to remote villages. Pesantren as Islamic education institutions have become a necessity to improve in many ways, so that they can become an alternative education system in the future and can play a role in creating social support for the development of Islamic education.Keywords: existence, pesantren, Islamic education